2022
DOI: 10.1039/d2py00542e
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive studies of continuous flow reversible addition–fragmentation chain transfer copolymerization and its application for photoimaging materials

Abstract: We demonstrate thorough studies of reversible addition-fragmentation chain transfer (RAFT) copolymerization of industrially relevant functional monomers utilizable for chemically amplified resist systems using an industry-friendly solvent, propylene glycol monomethyl ether,...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 84 publications
(125 reference statements)
1
9
0
Order By: Relevance
“…Furthermore, the concept of flow chemistry could be utilized for the synthesis of well-defined block copolymers. [44] Additionally, it was possible to using sonication within a flow tubular microreactor for the performance of a controlled radical polymerization (see Figure 1). [45] Flow chemistry in polymer research is currently still in its infancy but will certainly continue to develop accordingly over the next years and new approaches will be investigated.…”
Section: Flow-chemistrymentioning
confidence: 99%
“…Furthermore, the concept of flow chemistry could be utilized for the synthesis of well-defined block copolymers. [44] Additionally, it was possible to using sonication within a flow tubular microreactor for the performance of a controlled radical polymerization (see Figure 1). [45] Flow chemistry in polymer research is currently still in its infancy but will certainly continue to develop accordingly over the next years and new approaches will be investigated.…”
Section: Flow-chemistrymentioning
confidence: 99%
“…Recent studies on the polymerization under continuousflow conditions have shown their significant advantages compared to the batch process: scalability of photomediated processes; [30][31][32] increased heat and mass transfer properties, 31,33 especially under conditions of dispersion polymerization; 22,34 increased light irradiation efficiencies; 35 unprecedentedly high conversions achieved in a short time; 19,23,32,34,[36][37][38][39] narrower molecular weight distribution; 23,34 simplification of multistage syntheses by using a series or parallel connection of several reactors; 20,31,[39][40][41][42] automation capability. 43 Most of these advantages arise from the ability to precisely control reaction parameters (temperature, reaction time) in a small volume.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, a flow reactor has a high surface area to volume ratio, shorter diffusion pathways and excellent heat and mass transfer, which can lead to a shorter reaction time and a higher yield. [14][15][16][17][18][19][20][21][22][23][24][25][26] The use of flow systems in Stille polycondensation of conjugated polymers has been shown to improve the reproducibility of the process, leading to higher-quality products and better device performance. [27][28][29][30][31] Additionally, recent studies have focused on identifying key factors that affect molecular weight in the synthesis of conjugated polymers in flow.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, a flow reactor has a high surface area to volume ratio, shorter diffusion pathways and excellent heat and mass transfer, which can lead to a shorter reaction time and a higher yield. 14–26…”
Section: Introductionmentioning
confidence: 99%